Cytotoxicity Assay of 2,4-Dihydroxide-4’-Methoxychalcone Against Cervical (HeLa) Cancer Cell by MTT Assay - Novia Suryani; Sabirin Matsjeh; Mutmainah Mutmainah; Daratu Eviana Kusuma Putri Eviana Kusuma Putri; Damayanti Iskandar; Syarifah Asyura (Biota, 2020)
Chalcone is one of the phenolic group secondary metabolic with numerous biological activity. Many studies have shown that chalcone derivatives compound has anticancer, anti-inflammatory, antimalarial, and antibacterial activities. The purpose of this research was to study the prediction potency unsaturated carbonyl system of chalcone derivative against the HeLa cell by MTT assay. Those activities assumed can inhibit the mechanism action of NF-kB that caused cervical cancer. The 2,4-dihydroxide-4’-methoxychalcone has done synthesis as a target compound by a sonochemical for 7 hours. The results showed that chalcone derivative most active against the HeLa cell.